Pengaruh Model Problem Based Learning (PBL) Terhadap Aktivitas Dan Prestasi Belajar Siswa Materi Persamaan Garis Lurus Kelas VIII SMPN 1 Aikmel Tahun Pelajaran 2022/2023 - Hammad Al Haetami; Nurul Hikmah; Junaidi; Ketut Sarjana (FKIP Universitas Mataram, 2024)
This study aims to determine the effect of the Problem-Based Learning (PBL) model on student activity and learning achievement. The research was conducted at SMP Negeri 1 Aikmel during the 2022/2023 academic year. This is a quantitative study with a quasi-experimental approach using a posttest-only non-equivalent control group design. The population in this study consists of all eighth-grade students at SMP Negeri 1 Aikmel for the 2022/2023 academic year. The sample includes 30 students from class VIII A and 30 students from class VIII C, which serve as the experimental and control groups, respectively, selected based on the similar or homogeneous abilities of both classes. Data on student activity and learning achievement after the treatment were collected using questionnaires and tests. Quantitative data analysis was performed using multivariate Hotelling's T² test, followed by Bonferroni t-tests, and then an independent samples t-test. The three statistical tests yielded a significance value of 0.000 < 0.05, leading to the rejection of the null hypothesis (H0), indicating a significant difference in the mean scores between the two groups in terms of student activity and learning achievement, both simultaneously and separately. The results of the study show that the Problem-Based Learning (PBL) model has an impact on student activity and learning achievement in the topic of linear equations for eighth-grade students at SMP Negeri 1 Aikmel during the 2022/2023 academic year.